Regional Approaches to the Energy Transition A Multidisciplinary Perspective - Gromek-Broc, Katarzyna (Cham : Springer International Publishing : Imprint: Springer, 2023)
The book"Regional Approaches to the Energy Transition", discusses the key challenges the energy transition is facing at the European and International level. It is an edited collection gathering contributions from the experts in the field bringing together internationally renowned scholars, researchers, EU officials to address the current trends in the energy transition and its dilemmas. The book places the energy transition in a wide interdisciplinary context. It looks at energy policies, legal framework, regional strategies and the difficulties in their implementation. It argues for a regional approach to the energy transition, questioning at the same time the strategies and measures put forward for its realisation. The subject matter is topical, considering recent themes that occupy global and European political agendas. In a nutshell, the volume offers insights into regional regulations, public policies and local practices on the use of clean energy. It looks first at the EU commitment and its initiatives providing some examples from the Member States. Furthermore, it offers a comparative perspective and discusses the different approaches to the energy transition from Latin America, China, Africa and Australia. It covers a wide range of topics such as the EU renewable energy policies, Green Deal and regionalisation, energy auctions in the EU, environment in contemporary constitutionalism, Human Rights considerations, the Scandinavian perspective, practical examples from Italy and Spain. Moreover, it also considers the global context, looking at State and Market in China's coal-to-gas transition, tendencies of legal regulation in the sphere of renewable energy in Russia, the energy transition in Latin-American countries, regional approach to the energy transition and electricity access initiatives in Sub-Saharan Africa, and transnationalism and the regional approach to the energy transition in Australia. The systematisation that this book offers and the exchange of good practices and experiences are useful tools for the key players to seriously engage with a just and sustainable energy transition. The proposed book is a reference and study material for academics and students, but also for the policy makers, officials and practitioners dealing with the energy transition. It provides some answers, potential solutions and alternatives to the main problems that the energy sector is facing worldwide.
The European Union and Renewable Energy Policies -- A Few Words on the Energy-related Considerations -- The Environment in Contemporary Constitutionalism -- The Italian Energy Transition in a Human Rights Perspective -- Beyond the Energy Transition and Towards a Just Transition -- Wind of Change: A Scandinavian Perspective on Energy Transition and the 'Greenification' of the Oil and Gas Sector -- Green Deal and Regionalisation -- Energy Auction in the European Union with Specific Reference to Member State Practice in Germany and France -- The Energy Transition and the Use of EU Funds in the Spanish and Italian Legal Systems -- State and Market in China's Coal-to-Gas Transition -- Tendencies in Regulatory Framework of Renewable Energy in Russia -- Energy Ttransition and Latin-American Countries: example Cuba: Looking for Interconnections with Food Sovereignty -- Is there a Regional Approach to the Energy Transition in Sub-Saharan Africa? -- Ineluctable Transnationalism, and the Regional Approach to the Energy Transition -- From Coal to Climate Change: An Australian Perspective on the Energy Transition -- A Comparative Analysis of Electricity Access Initiatives in Sub-Saharan Africa.
Keywords: International law; Environmental law, International; Law -- Europe; Renewable energy sources; Economics; Power resources; Energy policy; Public International Law; International Environmental Law; European Law; Renewable Energy; Political Economy of Energy; Energy System Transformation